A Intuição na Tomada de Decisão em Desastres - Cerqueira, Alexandre dos Santos (2020)
Disasters are unforeseen events with high negative consequences, including the loss of life and property of organizations or communities, WHERE decisions are under pressure in a real scenario that changes suddenly. Earthquakes, tsunamis, fires and floods